Method for preparing multi-carbon product by electrically reducing carbon dioxide

By using self-assembled spherical copper nanoparticle catalyst and nickel iron or iridium oxide anode in membrane electrode electrolytic cells, combined with a method of moderately increasing the moisture pressure on the cathode side, the Faraday efficiency and stability of multi-carbon products under high current density in the prior art are solved. The problem of insufficient results has achieved efficient and stable electroreduction of carbon dioxide to make ethylene and ethanol.

CN119465226APending Publication Date: 2025-02-18XIAMEN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411590305.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing electrically reducing carbon dioxide technology is difficult to maintain the Faraday efficiency and stability of high polycarbon products under high current density, and there are problems with high ohmic internal resistance and catalyst stability.

Method used

Self-assembled and surface-roughened spherical copper nanoparticle catalyst is used as the cathode, combined with nickel iron or iridium oxide as the anode, and electrocatalytic reaction is carried out by controlling the feed moisture pressure on the cathode side to improve the generation rate and Faraday efficiency of the multi-carbon product.

Benefits of technology

The Faraday efficiency of 80% of the multi-carbon product is achieved at a high current density, and the catalyst can operate stably for 350 hours at an industrial current density of 250 mA, significantly improving the efficiency and stability of electroreducing carbon dioxide to ethylene and ethanol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465226A_ABST
    Figure CN119465226A_ABST
Patent Text Reader

Abstract

A method for preparing a multi-carbon product by electrically reducing carbon dioxide relates to the technical field of energy catalysis and is carried out in a membrane electrode electrolytic tank, and self-assembled spherical copper nanoparticles with rough surfaces are used as a cathode catalyst. By introducing a mixed gas of carbon dioxide and water into the cathode side, the carbon dioxide is electrically reduced to prepare a multi-carbon product. By adjusting the moisture pressure, the catalytic performance is improved, and the problems of low selectivity and low stability under high current density are solved. Cuprous oxide and metal copper are adopted under the reaction potential, and high reaction activity and ethylene and ethanol selectivity are shown. Under the conditions that the water pressure is 2.7 kPa and the current density is 1.0 A # imgabs0 #, the Faraday efficiency of a multi-carbon product reaches 80%, the Faraday efficiency of ethylene reaches 58% at most, and an excellent carbon dioxide reduction effect is shown. The method is simple in preparation and easy to implement, and the catalyst is excellent in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy catalysis technology, and in particular to a method for preparing multi-carbon products by electro-reduction of carbon dioxide. Background Art

[0002] Electrocatalytic reduction of carbon dioxide can generate a variety of carbon-containing products, such as carbon monoxide, methane, formate, ethylene and ethanol. Comparing the energy input cost and market price of different products, the added value of the products obtained per kWh of electrical energy input for the preparation of ethylene and ethanol is significantly higher than that of single-carbon products. As an important basic chemical raw material, ethylene is widely used in the production of plastics, synthetic fibers and other organic chemical products; ethanol has important uses in the fields of medicine, fuel and chemical solvents. At present, the production of ethylene and ethanol in industry mainly relies on petrochemical processes. These methods not only have high energy consumption, but also are accompanied by a large amount of carbon emissions, causing serious environmental pollution. Therefore, the development of mild, energy-saving and environmentally friendly electrochemical methods to directly convert carbon dioxide into ethylene and ethanol has great research and application prospects.

[0003] However, although the existing electroreduction of carbon dioxide to produce ethylene and ethanol has high Faradaic efficiency and economic value in theory, it still faces many challenges in practical application. First, the generation of multi-carbon products with high Faradaic efficiency can usually only be achieved at a lower current density, resulting in a low product generation rate that is difficult to meet the needs of industrial scale. Secondly, there is a thicker solution layer between the cathode and the anode in the existing flow cell system, resulting in a higher ohmic internal resistance. The electroreduction reaction of multi-carbon products usually requires the application of a relatively high voltage, which not only increases energy loss, but also places higher requirements on the stability of the catalyst. Most catalysts show poor stability under high current density and long-term operation conditions, which limits their application in actual production.

[0004] Therefore, in order to address the existing technical problems in the electroreduction of carbon dioxide to produce ethylene and ethanol, developing a new reaction process and catalyst that can maintain high multi-carbon product Faraday efficiency and stability at high current density has become the key to improving the technical level of electroreduction of carbon dioxide to produce ethylene and ethanol. Summary of the invention

[0005] The purpose of the present invention is to solve the above-mentioned problems in the prior art and to provide a method for producing multi-carbon products by electro-reduction of carbon dioxide, which can significantly improve the efficiency and stability of electro-catalytic reduction of carbon dioxide to produce multi-carbon products such as ethylene and ethanol, promote the development of green chemical industry and sustainable energy, and has broad application prospects and important industrial significance.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme:

[0007] A method for electroreduction of carbon dioxide to prepare multi-carbon products, comprising the steps of carrying out an electrocatalytic reaction in a membrane electrode electrolyzer, using a self-assembled and surface-roughened spherical copper nanoparticle catalyst as a cathode, nickel iron or iridium oxide loaded on foamed nickel, titanium felt or titanium mesh as an anode, and an anion exchange membrane as a diaphragm; feeding a mixed feed of carbon dioxide and water into the cathode side, applying a negative potential or a negative current, and realizing electroreduction of carbon dioxide to prepare multi-carbon products; wherein the catalytic performance is improved by controlling the feed water partial pressure on the cathode side.

[0008] In the present invention, at room temperature, the water partial pressure is not higher than 3.0 kPa; when the reaction is carried out under heating conditions, the water partial pressure is adjusted according to the specific reaction temperature.

[0009] In the present invention, the applied current density is 0.01 ~ 1.5 A ; The feed flow rate of carbon dioxide and water mixture is 1~100 mL .

[0010] In the present invention, the electrolyte of the membrane electrode electrolytic cell is selected from at least one of KOH, NaOH, KHCO3, NaHCO3, K2SO4 and Na2SO4; the electrolyte concentration is 0.005~32M.

[0011] The self-assembled and surface-roughened spherical copper nanoparticle catalyst is composed of a spherical structure formed by self-assembly of copper nanoparticles, has a roughened surface, and comprises cuprous oxide and metallic copper at a reaction potential.

[0012] The preparation of the self-assembled and surface-roughened spherical copper nanoparticle catalyst comprises the following steps: dissolving a copper salt in an organic solvent, stirring and transferring the mixture to an autoclave for solvent thermal treatment, and finally centrifuging, washing and drying.

[0013] The organic solvent is selected from one or more of methanol, ethanol, ethylene glycol and N, N-dimethylformamide.

[0014] The copper salt is selected from one or more of copper nitrate, copper acetate, copper chloride and copper acetylacetonate.

[0015] The molar volume ratio of the copper salt to the organic solvent is 0.5-4 mmol:60-90 ml.

[0016] The temperature of the solvent thermal treatment is 130-200°C and the time is 2-6 hours.

[0017] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0018] 1. Simple preparation method and high performance: The catalyst preparation method of the present invention is easy to operate. Compared with the existing copper-based catalysts, especially in membrane electrode electrolyzers, the prepared catalyst has a high performance of up to 1.0 A. At a current density of 1.5 A, the Faraday efficiency of multi-carbon products was 80%, and the current density of multi-carbon products was increased to 0.8 A. , showing significantly excellent performance.

[0019] 2. Excellent working stability: In the existing electrocatalytic carbon dioxide reduction system, the cuprous oxide in the copper catalyst is difficult to exist stably in the membrane electrode electrolyte mode, and it is difficult to maintain the Faraday efficiency of high multi-carbon products at high current density. The cuprous oxide in the copper catalyst of the present invention can exist stably under high potential and high current density conditions. At an industrial current density of 1.5 MW, the catalyst can operate stably for 350 hours, and the Faraday efficiency of multi-carbon products remains stable. Therefore, the catalyst of the present invention not only has excellent electrocatalytic activity, but also has excellent working stability.

[0020] 3. Optimized catalyst interface improves reaction performance: The catalyst of the present invention has a rich interface between Cu2O and metallic copper. By appropriately increasing the water partial pressure in the cathode feed carbon dioxide in the membrane electrode electrolyzer, the formation of multi-carbon products can be promoted. This is mainly due to the fact that the Cu⁺ ions at the interface can effectively promote the activation of water to form active hydrogen species, promote the hydrogenation of adsorbed CO to form adsorbed CHO intermediates, and couple with adsorbed CO to form adsorbed OCCHO species. This optimized interface structure significantly improves the generation rate of multi-carbon products. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 : The in-situ X-ray diffraction (XRD) patterns of the self-assembled and surface-roughened spherical copper nanoparticle catalyst prepared in Example 1 of the present invention under different voltage conditions are shown.

[0022] Figure 2 : shows a scanning electron microscope (SEM) image of the self-assembled and surface-roughened spherical copper nanoparticle catalyst prepared in Example 1 after the reaction.

[0023] Figure 3 : Presents the in situ Raman spectra (Raman graphs) of the self-assembled and surface-roughened spherical copper nanoparticle catalyst prepared in Example 1 at different potentials in a heavy oxygen water labeled solution.

[0024] Figure 4 : Shows the in-situ X-ray absorption near-edge structure (XAFS) spectra of the self-assembled and surface-roughened spherical copper nanoparticle catalyst prepared in Example 1 under different voltages.

[0025] Figure 5 : It shows the distribution of electrocatalytic carbon dioxide reduction products under different voltages when the catalyst prepared in Example 1 is in a membrane electrode electrolyzer, using 0.1 M KHCO3 solution as the anode electrolyte and the cathode water partial pressure is 2.7 kPa.

[0026] Figure 6 : The reaction current density of electrocatalytic carbon dioxide reduction at different voltages for the catalyst prepared in Example 1 in a membrane electrode electrolyzer using 0.1 M KHCO3 solution as the anode electrolyte when the cathode water partial pressure is 0, 1.4, 2.7 and 3.0 kPa, respectively.

[0027] Figure 7 : The Faraday efficiency of multi-carbon products formed by electrocatalytic reduction of carbon dioxide under different voltages is demonstrated when the catalyst prepared in Example 1 is used in a membrane electrode electrolyzer with 0.1 M KHCO3 solution as the anode electrolyte and the cathode water partial pressures are 0, 1.4, 2.7 and 3.0 kPa, respectively.

[0028] Figure 8 : The Faraday efficiency of byproduct hydrogen formed during electrocatalytic reduction of carbon dioxide at different voltages when the catalyst prepared in Example 1 is used in a membrane electrode electrolyzer using 0.1 M KHCO3 solution as the anode electrolyte and the cathode water partial pressure is 0, 1.4, 2.7 and 3.0 kPa, respectively.

[0029] Fig. 9 : The formation rate of multi-carbon products formed by electrocatalytic reduction of carbon dioxide at different voltages is demonstrated when the catalyst prepared in Example 1 is used in a membrane electrode electrolyzer with 0.1 M KHCO3 solution as the anode electrolyte and the cathode water partial pressure is 0, 1.4, 2.7 and 3.0 kPa, respectively.

[0030] Fig.10 : Demonstrates the reaction stability of the self-assembled and surface-roughened spherical copper nanoparticle catalyst prepared in Example 1.

[0031] Fig.11 : The distribution of electrocatalytic carbon dioxide reduction products at different voltages is shown when the catalyst prepared in Example 1 is used in a membrane electrode electrolyzer with 1.0 M KOH solution as the anode electrolyte.

[0032] Fig.12: It shows the generation rate of multi-carbon products formed by electrocatalytic reduction of carbon dioxide at different voltages when the catalyst prepared in Comparative Example 1 is used in a membrane electrode electrolyzer with 0.1 M KHCO3 solution as the anode electrolyte and the cathode water pressure is 0 and 2.7 kPa respectively.

[0033] Fig.13 : It shows the generation rate of multi-carbon products formed by electrocatalytic reduction of carbon dioxide at different voltages when the catalyst prepared in Comparative Example 1 is used as the anode electrolyte in a membrane electrode electrolyzer and the cathode water pressure is 2.7 kPa.

[0034] Fig.14 : The distribution of electrocatalytic carbon dioxide reduction products at different potentials of the catalyst prepared in Example 1 in a flow-type electrolytic cell using 1.0 M KOH solution as the cathode and anode electrolytes, respectively, is shown. DETAILED DESCRIPTION

[0035] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0036] Example 1

[0037] The method for preparing a self-assembled and surface-roughened spherical copper nanoparticle catalyst comprises the following steps:

[0038] S1: Dissolve Cu(NO3)2·2.5 H2O (0.5 g) in 75 mL N, N-dimethylformamide and stir for 15 min to ensure that copper nitrate is completely dissolved. Then, transfer the solution to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, seal it, and perform solvothermal treatment at 160 °C for 4 h.

[0039] S2: After the solvent thermal treatment, the product is washed with deionized water and ethanol and dried to obtain a powdery self-assembled spherical copper nanoparticle catalyst with roughened surface.

[0040] Carbon dioxide reduction method:

[0041] An electrocatalytic reaction is carried out in a membrane electrode electrolyzer, and a self-assembled and surface-roughened spherical copper nanoparticle catalyst is used as a cathode. The catalyst can be coated on a gas diffusion layer or an anion exchange membrane, and the catalyst is located between the anion exchange membrane and the gas diffusion layer; nickel iron or iridium oxide is loaded on nickel foam, titanium felt or titanium mesh as an anode, and the anion exchange membrane is used as a diaphragm; a mixed feed of carbon dioxide and water is passed into the cathode side, and a negative potential or negative current is applied to achieve electroreduction of carbon dioxide to multi-carbon products; wherein the catalytic performance is improved by controlling the water partial pressure of the feed on the cathode side.

[0042] The carbon dioxide reduction method of this embodiment is described in detail below.

[0043] Preparation of cathode gas diffusion electrode: 6 mg of self-assembled and surface roughened spherical copper nanoparticle catalyst, 3 μL Nafion solution and 35 μL aQAPS-S 14 The solution was dispersed in 200 μL of a mixed solution of isopropanol-water (volume ratio 3:1) and ultrasonically dispersed for 1 h to obtain a uniform catalyst ink. 200 μL of the catalyst ink was coated on the gas diffusion layer four times using a pipette and dried at 60 °C for 0.5 h to obtain a cathode gas diffusion electrode. The catalyst loading was 1.5 mg .

[0044] Assembly of the membrane electrode electrolyzer: Two polytetrafluoroethylene (PTFE) gaskets were placed between the cathode and anode flow plates to prevent short circuits. The cathode gas diffusion electrode (2 cm × 2 cm), anion exchange membrane (4 cm × 4 cm), and anode IrO x / Ti mesh (3 cm × 3 cm) was pressed together. CO2-H2O mixed gas (typical flow rate was 50 mL ), the partial pressure of H2O was controlled by a humidifier to be 0 kPa, 1.4 kPa, 2.7 kPa, and 3.0 kPa, respectively. A 0.1 M KHCO3 aqueous solution was used as the anolyte, and its circulation flow rate was 2 mL unless otherwise specified. .

[0045] Electrochemical test: The electrolysis experiment and data acquisition were performed using the Ivium-4-Stat electrochemical workstation and Iviumsoft software. When evaluating the CO2 reduction reaction performance, a constant voltage of 2.3 V was first applied for 10 min to establish a stable gas-liquid transmission channel, and then the voltage was increased by 0.1 V every 5 min until the target value was reached. All test experiments were carried out at room temperature.

[0046] Experimental results and analysis:

[0047] Figure 1 The in-situ XRD patterns of the self-assembled and surface-roughened spherical copper nanoparticle catalyst prepared in Example 1 of the present invention under different voltages are shown. It can be observed from the diffraction pattern that after the voltage is applied, the diffraction peak of copper oxide disappears, the diffraction peak of metallic copper appears, and the peak of cuprous oxide gradually weakens. However, after reacting for 5 h at a voltage of 3.8 V, a small amount of cuprous oxide still exists, indicating that the catalyst is mainly composed of metallic copper and a small amount of cuprous oxide at the reaction potential.

[0048] Figure 2 The SEM image of the self-assembled and surface-roughened spherical copper nanoparticle catalyst after the reaction prepared in Example 1 is shown. The SEM image shows that the catalyst is composed of small particles with a diameter of about 10 to 20 nm, forming large spherical particles of 100 to 150 nm, and relatively loose small particles are distributed on the surface.

[0049] Figure 3 The in-situ Raman images of the self-assembled and surface-roughened spherical copper nanoparticle catalyst prepared in Example 1 at different potentials in a heavy oxygen water labeled solution are presented. Under the open circuit voltage, there is a and 620 The vibration peak of Cu2O gradually moves to a lower wave number as the potential shifts negatively, and finally stabilizes at 500 and 600 This indicates that the catalyst Cu2O Gradually replaced by , indicating that the cuprous oxide present at the reaction potential is formed in situ rather than as a residue.

[0050] Figure 4 The in-situ XAFS graphs of the self-assembled and surface-roughened spherical copper nanoparticle catalyst prepared in Example 1 of the present invention under different voltages in a membrane electrode electrolyzer are shown. The XANES results show that as the cell voltage increases from 3.0 V to 3.8 V, the Cu K edge of the self-assembled and surface-roughened spherical copper nanoparticle catalyst slightly shifts toward the position of the Cu foil, but even after 5 h of CO2 reduction reaction at 3.8 V, its position is still between the Cu foil and Cu2O, indicating that the average oxidation state of copper is between 0 and +1. Under the same electrolysis conditions, the Cu K edge of the catalyst in Comparative Example 1 is almost the same as that of the Cu foil, which confirms that the Cu in the catalyst in Comparative Example 1 is in a metallic state.

[0051] Figure 5 The distribution of electrocatalytic carbon dioxide reduction products at different voltages when the catalyst prepared in Example 1 uses 0.1 M KHCO3 solution as the anode electrolyte and the cathode CO2 water partial pressure is 2.7 kPa is shown. It can be seen that as the applied voltage gradually increases, the Faraday efficiency of its multi-carbon products gradually increases. In particular, at a voltage of 3.8 V, the current density reaches 1.0 A The Faraday efficiency of multi-carbon products reached 80%, mainly producing ethylene and ethanol. The generation rate of multi-carbon products reached 2.47 mmol .

[0052] Figure 6The self-assembled and surface-roughened spherical copper nanoparticle catalyst prepared in Example 1 of the present invention is shown. The reaction current density of electrocatalytic carbon dioxide reduction at different voltages is shown when 0.1M KHCO3 is used as the anolyte and the cathode water partial pressure is 0 kPa, 1.4 kPa, 2.7 kPa and 3.0 kPa respectively. The experimental results show that when the cathode water partial pressure increases from 0 kPa to 2.7 kPa, the total reaction current density at different cell pressures increases, especially when the cell pressure is 3.8 V, the reaction current density increases from 0.8 A to 1.4 A. Increase to 0.9 A and 1.0 A When the water partial pressure was further increased to 3.0 kPa, the reaction current density at each cell voltage decreased compared with that at 2.7 kPa, especially at 3.8 V cell pressure, the current density dropped to 0.85 A. This indicates that, for the catalyst prepared in Example 1 of the present invention, when tested in a membrane electrode electrolyzer, moderately increasing the water partial pressure can effectively increase the current density of the carbon dioxide reduction reaction.

[0053] Figure 7 The Faraday efficiency of multi-carbon products formed by electrocatalytic carbon dioxide reduction reaction under different voltages under the same conditions is demonstrated. The experimental results show that when the CO2 water partial pressure at the cathode is increased from 0 kPa to 2.7 kPa, the Faraday efficiency of multi-carbon products under different cell pressures is improved, especially when the cell pressure is 3.8 V, the Faraday efficiency of multi-carbon products is increased from 68% to 73% and 80% in sequence. However, when the water partial pressure is further increased to 3.0 kPa, the Faraday efficiency of multi-carbon products under different cell pressures is reduced compared with the result when the water partial pressure is 2.7 kPa, especially at 3.8V cell pressure, the Faraday efficiency of multi-carbon products is reduced to 70%. This shows that for the catalyst prepared in Example 1 of the present invention, moderately increasing the water partial pressure can effectively improve the Faraday efficiency of carbon dioxide reduction reaction to form multi-carbon products.

[0054] Figure 8The Faraday efficiency of the byproduct hydrogen generated by the electrocatalytic carbon dioxide reduction reaction under the same conditions is shown. The experimental results show that when the cathode water partial pressure is increased from 0 kPa to 2.7 kPa, the Faraday efficiency of hydrogen products under different cell pressures is reduced, especially when the cell pressure is 3.8 V, the Faraday efficiency of byproduct hydrogen is reduced from 22% to 19% and 15% in sequence. When the water partial pressure is further increased to 3.0 kPa, the hydrogen Faraday efficiency at different voltages is increased compared to 2.7 kPa, especially at 3.8V cell pressure, the hydrogen product Faraday efficiency is increased to 20%. This shows that for the catalyst prepared in Example 1 of the present invention, moderately increasing the water partial pressure can effectively reduce the Faraday efficiency of the carbon dioxide reduction reaction to generate byproduct hydrogen, that is, suppress the progress of the hydrogen evolution side reaction.

[0055] Fig. 9 The experimental results show that when the water pressure of the cathode increases from 0 kPa to 2.7 kPa, the generation rate of multi-carbon products at different cell pressures increases, especially when the cell pressure is 3.8 V, the generation rate of multi-carbon products increases from 1.67 mmol Increased to 1.96 mmol and 2.47 mmol When the water pressure was further increased to 3.0 kPa, the generation rate of multi-carbon products at different cell pressures decreased compared with that at 2.7 kPa, especially at 3.8V cell pressure, the generation rate of multi-carbon products dropped to 1.70 mmol This indicates that, for the catalyst prepared in Example 1 of the present invention, moderately increasing the partial pressure of water can improve the activity of the carbon dioxide reduction reaction and promote the formation of multi-carbon products.

[0056] Fig.10 The reaction stability of the self-assembled and surface-roughened spherical copper nanoparticle catalyst prepared in Example 1 of the present invention is demonstrated. The experimental results show that the catalyst can be used at 250 mA using 0.1 M KHCO3 as the anolyte. After continuous operation for 350 h at the same current density, the Faradaic efficiency of multi-carbon products remained above 70%.

[0057] Embodiment 2:

[0058] The experiment was carried out according to the method of Example 1, except that the electrolyte used in the test was replaced with 1.0 MKOH, and the other conditions were the same as in Example 1.

[0059] Fig.11The distribution of electrocatalytic carbon dioxide reduction products of the self-assembled surface roughened spherical copper nanoparticle catalyst prepared in Example 1 of the present invention at different voltages is shown. The results show that using 1.0 M KOH instead of 0.1 M KHCO3 significantly reduces the internal resistance of the battery and achieves a higher current density at a lower voltage. The current density reaches 0.8A at 3.1 V. , the Faraday efficiency of multi-carbon products reached 80%. The generation rate of multi-carbon products reached 2.05 mmol .

[0060] Embodiment 3:

[0061] Different from Example 1, 0.5 mmol Cu(NO3)2·2.5 H2O was dissolved in 75 mL N, N-dimethylformamide.

[0062] The performance of the electrocatalytic CO2 reduction reaction was evaluated in a membrane electrode electrolyzer. The test method was the same as in Example 1. The water partial pressure was 2.7 kPa, a voltage of 3.8 V was applied for 0.5 h, the Faraday efficiency of the multi-carbon product was 50%, and the generation rate was 1.56 mmol .

[0063] Embodiment 4:

[0064] Different from Example 1, 1 mmol Cu(NO3)2·2.5 H2O was dissolved in 75 mL N, N-dimethylformamide.

[0065] The performance of the electrocatalytic CO2 reduction reaction was evaluated in a membrane electrode electrolyzer. The test method was the same as in Example 1. The water partial pressure was 2.7 kPa, and a voltage of 3.8 V was applied for 0.5 h. The Faraday efficiency of the multi-carbon product was 70%, and the generation rate was 2.06 mmol. .

[0066] Embodiment 5:

[0067] Different from Example 1, 3 mmol Cu(NO3)2·2.5 H2O was dissolved in 75 mL N, N-dimethylformamide.

[0068] The performance of the electrocatalytic CO2 reduction reaction was evaluated in a membrane electrode electrolyzer. The test method was the same as in Example 1. The water partial pressure was 2.7 kPa, and a voltage of 3.8 V was applied for 0.5 h. The Faraday efficiency of the multi-carbon product was 61%, and the generation rate was 1.78 mmol. .

[0069] Embodiment 6:

[0070] Different from Example 1, 4 mmol Cu(NO3)2·2.5 H2O was dissolved in 75 mL N, N-dimethylformamide.

[0071] The performance of the electrocatalytic CO2 reduction reaction was evaluated in a membrane electrode electrolyzer. The test method was the same as in Example 1. The water partial pressure was 2.7 kPa, and a voltage of 3.8 V was applied for 0.5 h. The Faraday efficiency of the multi-carbon product was 36%, and the generation rate was 1.12 mmol. .

[0072] Comparative Example 1:

[0073] 2 mmol Cu(NO3)2·2.5 H2O was dissolved in 75 mL N, N-dimethylformamide and stirred for 15 min to ensure that the copper nitrate was completely dissolved. Subsequently, the solution was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, sealed and subjected to solvent thermal treatment at 160 °C for 4 h. After solvent thermal treatment, the product was washed and dried with deionized water and ethanol, and further reduced with 5% H2-Ar mixed gas at 350 °C for 2 h. A powdered metallic copper catalyst was obtained. The carbon dioxide reduction test method, the assembly of the membrane electrode electrolyzer, and the electrochemical test were the same as in Example 1.

[0074] Experimental results and analysis:

[0075] Fig.12 The rate of electrocatalytic CO2 reduction to generate multi-carbon products at different voltages using the copper catalyst prepared in Comparative Example 1, when 0.1 M KHCO3 was used as the anolyte and the cathode water pressure was 0 kPa and 2.7 kPa, respectively. The results show that when the cathode water pressure increased from 0 kPa to 2.7 kPa, the generation rate of multi-carbon products at each cell pressure did not change significantly, especially at 3.8 V cell pressure, the generation rate of multi-carbon products was 0.5 mmol This shows that for the catalyst in Comparative Example 1, increasing the water partial pressure in the membrane electrode electrolyzer cannot improve the CO2 reduction reaction performance, especially has no obvious promoting effect on the formation of multi-carbon products. This further shows that for the catalyst in Example 1, moderately increasing the water partial pressure can effectively improve the CO2 reduction reaction performance and promote the formation of multi-carbon products.

[0076] Fig.13 The distribution of electrocatalytic CO2 reduction products at different voltages for the catalyst prepared in Comparative Example 1 is shown when 0.1 M KHCO3 solution is used as the anolyte and the cathode water partial pressure is 2.7 kPa. It can be seen that with the increase of the applied voltage, the Faraday efficiency of the multi-carbon product gradually increases, especially at 3.8 V, the current density reaches 1.0 A The Faraday efficiency of multi-carbon products reaches 45%, mainly producing ethylene and ethanol.

[0077] Comparative Example 2:

[0078] The powdered self-assembled spherical copper nanoparticle catalyst with roughened surface of Example 1 was used for the reduction of carbon dioxide in a flow-type electrolytic cell.

[0079] Carbon dioxide reduction test method:

[0080] Preparation of cathode gas diffusion electrode: 4.5 mg of self-assembled and surface roughened spherical copper nanoparticle catalyst, 2.25 μL Nafion solution and 26.25 μL aQAPS-S 14 The solution was dispersed in 150 μL of a mixed solution of isopropanol-water (volume ratio 3:1) and ultrasonically dispersed for 1 h to obtain a uniform catalyst ink. 150 μL of the catalyst ink was coated on the gas diffusion layer three times using a pipette and dried at 60 °C for 0.5 h to obtain a gas diffusion electrode with a catalyst loading of 1.5 mg. .

[0081] Assembly of the flow electrolysis cell: Two polytetrafluoroethylene (PTFE) gaskets were placed between the cathode and anode flow channels to prevent short circuits. The cathode gas diffusion electrode (1 cm × 3 cm), cathode electrolyte microchannel plate, anion exchange membrane (4 cm × 4 cm), and anode nickel foam (3 cm × 3 cm) were pressed together with a fixed tightening force of 3 N m. CO2 gas (flow rate of 50 mL) was introduced into the cathode. A solid Ag / AgCl electrode was used as the cathode reference electrode, and a 1.0 M KOH aqueous solution was used as the cathode and anode electrolytes, respectively, with a circulation flow rate of 10 mL .

[0082] Electrochemical test: Ivium-4-Stat electrochemical workstation and Iviumsoft software were used for electrolysis experiments and data acquisition. When evaluating the performance of CO2 reduction reaction, different cathode potentials were applied to control the reaction. All test experiments were carried out at room temperature.

[0083] Experimental results and analysis:

[0084] Fig.14 The product distribution of the electrocatalytic CO2 reduction reaction of the self-assembled and surface-roughened spherical copper nanoparticle catalyst prepared in Example 1 of the present invention in a flow-type electrolytic cell is shown. The results show that the reaction current density reaches 1.0 A when a voltage of -0.78 V (vs. RHE) is applied for 0.5 h. The Faraday efficiency of the multi-carbon product was 45% and the generation rate was 1.41 mmol .

Claims

1. A method for preparing multi-carbon products by electroreduction of carbon dioxide, characterized in that: An electrocatalytic reaction is carried out in a membrane electrode electrolyzer, with a self-assembled and surface-roughened spherical copper nanoparticle catalyst serving as the cathode, nickel iron or iridium oxide loaded on nickel foam, titanium felt or titanium mesh serving as the anode, and an anion exchange membrane serving as the diaphragm; a mixed feed of carbon dioxide and water is passed into the cathode side, and a negative potential or negative current is applied to achieve electroreduction of carbon dioxide to multi-carbon products; the catalytic performance is improved by controlling the feed water partial pressure on the cathode side.

2. The method for preparing multi-carbon products by electro-reduction of carbon dioxide according to claim 1, characterized in that: At room temperature, the water partial pressure is not higher than 3.0 kPa; when the reaction is carried out under heating conditions, the water partial pressure is adjusted according to the specific reaction temperature.

3. The method for preparing multi-carbon products by electro-reduction of carbon dioxide according to claim 1, characterized in that: The applied current density is 0.01 ~ 1.5 A ; The feed flow rate of carbon dioxide and water mixture is 1~100 mL .

4. The method for preparing multi-carbon products by electro-reduction of carbon dioxide according to claim 1, characterized in that: The electrolyte of the membrane electrode electrolytic cell is selected from at least one of KOH, NaOH, KHCO3, NaHCO3, K2SO4 and Na2SO4; the electrolyte concentration is 0.005~32M.

5. The method for preparing multi-carbon products by electro-reduction of carbon dioxide according to claim 1, characterized in that: The self-assembled and surface-roughened spherical copper nanoparticle catalyst is composed of a spherical structure formed by self-assembly of copper nanoparticles, has a roughened surface, and comprises cuprous oxide and metallic copper at a reaction potential.

6. The method for preparing multi-carbon products by electro-reduction of carbon dioxide according to claim 1, characterized in that: The preparation of the self-assembled and surface-roughened spherical copper nanoparticle catalyst comprises the following steps: dissolving a copper salt in an organic solvent, stirring and transferring the mixture to an autoclave for solvent thermal treatment, and finally centrifuging, washing and drying.

7. A method for preparing multi-carbon products by electro-reduction of carbon dioxide according to claim 6, characterized in that: The organic solvent is selected from one or more of methanol, ethanol, ethylene glycol and N, N-dimethylformamide.

8. The method for preparing multi-carbon products by electro-reduction of carbon dioxide according to claim 6, characterized in that: The copper salt is selected from one or more of copper nitrate, copper acetate, copper chloride and copper acetylacetonate.

9. The method for preparing multi-carbon products by electro-reduction of carbon dioxide according to claim 6, characterized in that: The molar volume ratio of the copper salt to the organic solvent is 0.5-4 mmol:60-90 ml.

10. The method for preparing multi-carbon products by electro-reduction of carbon dioxide according to claim 6, characterized in that: The temperature of the solvent thermal treatment is 130-200°C and the time is 2-6 hours.

Citation Information

Cited By

  • Series catalyst, preparation method and application of series catalyst in electroreduction of carbon dioxide

    CN121826783A